Characterization of Carica pubescens in Dieng Plateau, Central Java based on morphological characters, antioxidant capacity, and protein banding pattern - AINUN NIKMATI LAILY; SURANTO SURANTO; SUGIYARTO SUGIYARTO (Smujo International, 2012)
Abstract. Laily AN, Suranto, Sugiyarto. 2012. Characterization of Carica pubescens in Dieng Plateau, Central Java based on morphological characters, antioxidant capacity, and protein banding pattern. Nusantara Bioscience 4: 16-21. Carica pubescens Lenne & K. Koch is a species of fruit plant firstly cultivated in South America and has adapted to the highland environment, such as Dieng Plateau, Central Java (±2000 m asl). It has a narrow habitat range and limited or unknown intraspecies variation. Therefore, important information about the characters of the plants at various altitudes is needed, so that it is possible to extend its distribution through transplantation to other areas. Characterization can be performed based on morphological characters, chemical content, and protein banding patterns. This study aimed to describe the morphological characters, the chemical content (antioxidant capacity), and the pattern of protein bands by staining, using Coomassie brilliant blue on C. pubescens in the Dieng Plateau. The research was conducted in the villages of Kejajar (1400 m asl), Patak Banteng (1900 m asl.), and Sembungan (2400 m asl.). The observations of morphological characters were conducted in the field and continued in the laboratory. Morphological characters, the chemical content (antioxidant capacity), and the banding pattern of protein of C. pubescens were analyzed descriptively. The results showed that the morphological characters of C. pubescens in Dieng Plateau varied in stems, leaves, and fruits. The antioxidant capacity decreased with decreasing habitat altitude, 2400 m asl. altitude> 1900 m altitude> 1400 m asl.. The Protein banding patterns did not vary, but the pattern in C. Papaya was different. The uniformity of the pattern of protein bands showed that genetic stability in C. pubescens was not affected by environmental factors.